Composite Materials: Fatigue and Fracture, Second Volume 1989
DOI: 10.1520/stp10418s
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar Shear Fracture Toughness and Fatigue Thresholds for Composite Materials

Abstract: SUMMARY I;'S t a t i c and c y c l i c end-notched f l e x u r e (ENF) tests were conducted on three materials t o d e t e r m i n e t h e i r i n t e r l a m i n a r shear fracture toughness and f a t i g u e t h r e s h o l d s f o r d e l a m i n a t i o n i n terms o f l i m i t i n g v a l u e s of t h e mode I1 s t r a i n e n e r g y release r a t e , G I I , f o r delamination growth. Data were g e n e r a t e d f o r three d i f f e r e n t materials: a T300/BP907 g r a p h i t e epoxy, a n S2/SP250 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…Use of tough matrix systems was shown to greatly improve composites' damage tolerance [1], but unfortunately the accompanying reduction in Gnc/G~c for such materials necessitates the additional consideration of shearing modes in any fracture analysis. This is manifested under cyclic loading, where threshold Gnc values for tough resins may be as little as the mode I toughness of brittle epoxy resins [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Use of tough matrix systems was shown to greatly improve composites' damage tolerance [1], but unfortunately the accompanying reduction in Gnc/G~c for such materials necessitates the additional consideration of shearing modes in any fracture analysis. This is manifested under cyclic loading, where threshold Gnc values for tough resins may be as little as the mode I toughness of brittle epoxy resins [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The extensional modulus, E 11, in the longitudinal direction of the test specimen would control deformation of a homogenous material. However, it has been shown that the measured stiffness of this type of composite bending specimen is significantly less than that predicted by a simple bending model using a modulus value measured in tension [8]. In other words, the effective modulus for these specimens in bending is normally less than the value of modulus measured in tension.…”
Section: Choice Of Modulus For Toughness Measurementsmentioning
confidence: 71%
“…First, the moduli of these types of bending specimens vary significantly from specimen to specimen. For this reason, compliance calibration methods are suggested for both the DCB Mode I test [9] and the ENF Mode II test [8]. The type of compliance calibration used with the DCB specimen does not work with the MMB specimen because the delamination growth is not always stable.…”
Section: Choice Of Modulus For Toughness Measurementsmentioning
confidence: 99%
“…Moreover the effect of friction increases with span ratio [27,28]. Kageyama et al [12] have shown that the experimental compliance does not agree well with the theoretical one.…”
Section: Influence Of Frictionmentioning
confidence: 99%
“…One of the most accurate data reduction methods to determine delamination toughness from 4ENF test data is compliance calibration technique (as compared to beam theory and finite element analysis if the crack length is measured accurately). Because of that, it was shown that beam theory and finite element based data reduction techniques can produce errors in toughness values [27,28] due to the fact that it is difficult to accurately determine the bending stiffness of each test specimen. But compliance calibration data reduction is a direct method that assumes linear elastic behaviour and self-similar crack advance.…”
Section: Compliance Calibrationmentioning
confidence: 99%